Integrating Autonomous Vehicle Simulation Tools using SmartData - Hoffmann, José Luis Conradi; Horstmann, Leonardo Passig; Fröhlich, Antônio Augusto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2022)
This work proposes a SmartData-based middleware to integrate Autonomous Systems Simulators and external tools. The interface models the data used on a simulator and creates an intermediary layer between the simulator and the external tools by defining the inputs and outputs as SmartData. A message bus is used for communication between SmartData following their interest relations. Messages are exchanged following a specific protocol such as CAN, TSTP, and EtherCat. However, the architecture presented is agnostic of protocol. The presented interface eases the integration of the autonomous system simulation with other simulators (e.g., Network Simulators), Cloud services, fault injection mechanisms, Digital Twins, and Hardware-in-the-loop scenarios. Moreover, this interface allows transparent, runtime component replacement and time synchronization, the modularization of the components of the system, and the addition of security aspects in the simulation. After presenting the interface proposed, we present a case-study application with an autonomous vehicle simulation using CARLA and measure the end-to-end delay and overhead incurred in the simulation.